FEATURES OF THE FINANCIAL PLANNING TECHNOLOGY IN LOCAL GOVERNMENT - O. A. Ryabkov (Российский технологический журнал)
The article analyzes the characteristics that affect the formation of the revenue and expenditure sides of the budget of intracity municipal unions of Moscow. Shows the legal basis upon which the provisions on the formation and spending of budgetary funds by local authorities. The problems arising from the formation and execution of budgets of intracity municipal unions of Moscow. The evidence base for the considered problem based real figures taken from the budget execution reports municipality "Eastern Izmailovo" in Moscow. The ways of solving identified problems, which would increase the efficiency of the local governments. The article may be useful in the practical work of government bodies, as well as of particular interest for the control of the executive power. Without addressing these problems, the path of development of local self-government becomes a dead end, the inability to influence the improvement of the situation in the district generates apathy and indifference as the population, and among municipal employees.